Perbandingan Sifat Bahan Baku dan Pulp Kraft Geronggang (Cratoxylon arborescen) Alam dan Tanaman (Comparison the Properties of Raw Material and Kraft Pulp from Nature and Plantation of Geronggang Wood (Cratoxylon arborescen)) - Yeny Aprinis; Opik T Akbar; Kanti D Rizqiani (Jurnal Ilmu dan Teknologi Kayu Tropis, 2018)
Geronggang (Cratoxylum arborescen) is one of local wood in Riau peatlands has potential as raw material for pulp. This study aims to compare properties of raw material and kraft pulp  from nature and plantation of geronggang wood. The parameters observed were chemical properties, fibers dimension, and pulp properties. The comparison of the both geronggang properties were analyzed using T test. The results indicated that both geronggang wood nature and plantation showed similar chemical properties in term of extractives, cellulose, and hemicellulose, and fiber dimensions except lignin content. Kraft properties of both geronggang woods also have similar results of yield and Kappa number, except lignin content.